A cone beam computed tomographic analysis of the greater palatine foramen in a cohort of Sri Lankans - Manil C.N. Fonseka; P.V.Kalani S. Hettiarachchi; Rasika M. Jayasinghe; Ruwan D. Jayasinghe; C. Deepthi Nanayakkara (Elsevier, 2019)
Objectives: To determine the size and position of the Greater Palatine Foramen using CBCT Materials and method: GPF was evaluated on 50 CBCT's which were obtained at the Division of Oral Medicine and Radiology, FDS, University of Peradeniya, The distance of each GPF to the mid maxillary suture (MMS), Anterior Nasal Spine (ANS), relationship of the GPF to the molar teeth and diameter were measured in different orthogonal planes using measurement tools integrated to the CBCT software. Results: Mean diameter of the GPF in females and males were 3.72 mm for the right and 3.31 mm for the left and 4.56 mm and 4.30 mm. The antero-posterior distance measured from the ANS to mid GPF in axial sections among females was 45.70 mm and 44.81 mm for the right and left respectively whereas for males it was 48.37 mm and 47.6 mm. The distances in axial sections were 14.82 and 15.14 mm for right and left sides in females whereas in males it was 15.50 and 15.67 mm from the MMS. The same measurement in the coronal plane was 14.93 mm and 15.22 mm for females for the right and left GPF and was 15.63 mm and 15.49 mm in males respectively. There was a significant difference between the distance of ANS to the GPF on both sides and the diameters of GPF in both males and females (p < 0.005). Conclusion: A significant difference was seen between the mean distance from the ANS to the GPF in left and right sides and the diameter of the GPF on the sides among the genders.